Pharmacy students' experience towards didactic lectures and problem-based learning (PBL) / Norfaradila Mohamed - Mohamed, Norfaradila (2009)
Descriptive of course Problem-based learning (PBL) is an instructional method that is gaining popularity in health care education. Rationale for the use of PBL to better prepare health care providers for the future is provided. Implementation of a PBL model into a bachelor Pharmacy degree program is described, including examples of activities that may be helpful to others wishing to implement PBL. The steps the groups use in the PBL process have been amended to encourage students to link their discussion with clinical experience. This study was designed in order to assess pharmacy students' experience towards didactic lecture and PBL. The aim of this study was to explore students' perceptions and opinion regarding combination of didactic lecture and problem-based learning session are being conducted, to determine the factors those influence the students' perception regarding modified teaching program, to investigate whether there had been a valuable exchange of idea in small-group discussions and how well this may help them in the university examination and also to study students' knowledge and satisfaction with the problem-based learning program in their courses as new teaching module. Evaluation For the purpose of this study, all 179 students were requested to complete an evaluation questionnaire. Out of 279 of survey only 226 (81%) were returned.